2022
DOI: 10.3390/rs14174196
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Leaf Area Index of Inner Mongolia Grassland Based on Machine Learning Regression Algorithms Incorporating Empirical Knowledge

Abstract: Leaf area index (LAI) is one of the key biophysical indicators for characterizing the growth and status of vegetation and is also used in modeling earth system processes. Machine learning algorithms (MLAs) such as random forest regression (RFR), artificial neural network regression (ANNR) and support vector regression (SVR) based on satellite data have been widely used for the estimation of LAI. However, the selection of input variables has a great impact on the estimation performance of MLAs. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The slope gradient has a negligible effect on the FVC of forest and grassland in such areas. Shen [63] and De Castilho [64] also reported that topography has little influence on vegetation parameters, and biomass estimation results in regions with low topographic relief. Above 3000 m, the topographic undulation becomes more prominent with increasing altitude, resulting in reduced soil and water conservation capacity and a significant increase in the importance of slope gradient on the FVC of forests and grassland [61].…”
Section: Influence Of Topographic Features On Fvc Retrievalmentioning
confidence: 98%
“…The slope gradient has a negligible effect on the FVC of forest and grassland in such areas. Shen [63] and De Castilho [64] also reported that topography has little influence on vegetation parameters, and biomass estimation results in regions with low topographic relief. Above 3000 m, the topographic undulation becomes more prominent with increasing altitude, resulting in reduced soil and water conservation capacity and a significant increase in the importance of slope gradient on the FVC of forests and grassland [61].…”
Section: Influence Of Topographic Features On Fvc Retrievalmentioning
confidence: 98%
“…RF was chosen and used in this study because it is fast, insensitive to overfitting, and effective in handling data multicollinearity and dimensionality [99]. RF is renowned for being more accurate and outperforming other regression algorithms [100][101][102][103][104]. Above all, it offers various importance matrices in its computation, which provide valuable insights into the effects of each predictor variable on the response variable [105].…”
Section: Spatial Analysismentioning
confidence: 99%
“…The normalized difference phenology index (NDPI) was chosen to establish the relationship between LAI among different grassland types; we generated LAI reference maps in Google Earth Engine with a spatial resolution of 30 m, which we then upscaled to a spatial resolution of 500 m. The NDPI design differs from the NDVI in that it incorporates the shortwave-infrared (SWIR) band [30]. Our other study also found that NDPI contributed the most to LAI estimation among multiple factors, including vegetation indices, climate factors, soil factors, and topography factors [31]. For each grassland type, 75% of the sampling points were taken for modeling and 25% for validation, respectively, to determine the inversion model to generate LAI reference maps.…”
Section: Leaf Area Index Reference Mapsmentioning
confidence: 99%